Análise à evolução do IVA na Região Autónoma da Madeira (2005-2015) - Dias, P.; Magro, N.; undefined (XXVIII Jornadas Luso Espanholas de Gestão Científica, 2018)
This study analyse the evolution of value added tax (VAT) in the Autonomous Region of Madeira (ARM) between 2005 and 2015 comparing to the mainland Portugal and the Autonomous Region of the Azores (ARA). It was also analyse the changes that occurred in 2012 in the ARM and the impacts on tax efficiency. It was concluded that VAT variations are associated with unfavourable economic contexts and that VAT is a powerful political and governmental instrument. It was verified that the Autonomous Regions have high efficiency ratios, there’s an implicit association between the change in VAT rates and efficiency, a high increase in the normal VAT rate resulted a reduction of the efficiency ratio. It is also verifiable low efficiency in periods of economic crisis. Finally, it is observable, from the results obtained, that there is a tendency on improve efficiency due to the stabilization of VAT rates.